MORPHO-PHONOLOGICAL OF LOANWORDS IN LAMPUNG LANGUAGE FROM ARABIC - Amrulloh, Muhammad Afif; Humairo, Luluk (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2020)
The purpose of this discussion is to find out the process of changing loanwords and the form or type of loanwords that occur. The research method used is a descriptive method. This methodology focuses more on the “what” of the research subject rather than the “why” of the research subject. Data collection used in this study is content analysis and library techniques from literature sources such as dictionaries. Data analysis used in this study is the translational equivalent method. The results of this study found that the loanwords on Lampung language from Arabic through morphophonological processes in the form of sound attenuation, sound reinforcement, sound relaxation, addition of sound, reduction of multiple consonants, dissimilation, and aferesis. Then, the types of loanwords produced by the Lampung language from Arabic Language are in the form of full absorption patterns, partial absorption and pronunciation adjusment. This study contributes to the wealth of linguistic studies, especially Arabic and Lampung language which are widely spoken by the local community.